Singing wine glasses - Parupudi, Aarti (Kansas State University, 2015)
One among the many inventions of Benjamin Franklin is the Glass Armonica, a musical instrument whose sound source was a series of resonating glass vessels. However, the Irish musician Richard Pockrich is typically credited as the first to play an instrument composed of glass vessels, called the Glass Harp in 1741, by rubbing his fingers around the rims. In this project “Singing Wine Glasses”, the principle of Franklin’s glass armonica is demonstrated with a wine glass. One hand is used to hold the glass steady at the base. The rim of glass is gently pressed with a moistened finger of the other hand and drawn in a circle around. When the pressure and amount of moisture are just right, the slight friction between the finger and the rim of glass causes vibrations in the sides of the glass. At a particular frequency, called the resonant frequency, the sides of the glass will vibrate most easily. The resonant frequency of wine glasses is typically within the range of human hearing (20-20,000 Hz), so the resulting resonant vibration is heard as a tone. The glass starts to sing when the vibration gets the molecules moving at their natural frequency. The resonant frequency changes with the amount of water filled in the glass. This android application deals with virtual glasses that serve the purpose of wine glasses filled with different amounts of water. Swiping on the glass edges would produce music, as per Franklin’s principle. The users would be free to select the number of glasses they want to play, and the amount of water-level in each glass. This application would also come with an enhanced feature of sustaining a particular note until the finger is released from the glass.
Keywords: Android; Wine Glasses; Application; Glass Harp; Computer Science (0984)